Efektivitas Pengelolaan Koperasi Simpan Pinjam Dab Tukrau Kecamatan Kei Kecil Kabupaten Maluku Tenggara - Renwarin, Martinus; Renel, Yuliana (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
This writing is about how effective the management of the Dab Tukrau savings and loan cooperative in Kei Kecil District, Southeast Maluku Regency. The results of the research found through  Five indicators are indicator 1. The clarity of the goals to be achieved The results of the research show that this initiator has been fulfilled because it has met the elements of having clear goals, achievement targets and an evaluation meeting to find out the obstacles faced by the management and members of the DAB Tukrau Cooperative. The second indicator is 2. Careful planning. For this idifier, it was found that it was carried out by the management and still received supervision from the relevant agencies and cooperative expert assistants 3.Indicators for the preparation of the right peogram have been carried out well by the management and continue to receive assistance. 4. Facilities and Infrastructure indicators. According to the results of the study, it can be concluded that there are infrastructure suggestions prepared and the last 5. Surveillance indicators and control that is educational can be concluded that the existence of the activity in question produces a good effect for the cooperative management and members of the Dab Tukrau cooperative.